Are smartphones and tablets influencing the quality of sleep? An Italian answer (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Electronic media use may affect sleep health. The present study aimed to estimate the association between technological devices usage, especially mobile phone, during the evening/night and self-reported sleep disorders. Methods: The survey was conducted between June and September 2016. Anonymous self-reported questionnaire was distributed to the Italian general population and investigated demographic data, presence of sleep disorders and the use of electronic devices. Results: The analysis was based on 597 questionnaires. Mobile phone exposure has been associated with increased difficulty falling to sleep (p= 0.018). The use of mobile phones at bedtime was significantly related to self-reported sleep disturbance (p